Genital Tract Infections in an Isolated Community: 100 Women of the Príncipe Island. (13th November 2017) - Vieira-Baptista, Pedro; Grinceviciene, Svitrigaile; Bellen, Gert; Sousa, Carlos; Saldanha, Conceição; Broeck, Davy Vanden; Bogers, John-Paul; Donders, Gilbert
Abstract : Objective . To characterize the vaginal microbiome and the rate of sexually transmitted infections (STIs) in the women of Príncipe (São Tomé and Príncipe). Methods . Cross-sectional study of 100 consecutive women, invited for a free appointment and cervical cancer screening. A vaginal slide (wet mount microscopy) and a cervical sample (ThinPrep®) (Pap test, high risk human papillomavirus [HR-HPV], N . gonorrhea [NG], T . vaginalis [TV], and C . trachomatis [CT]) were obtained. Results . TV, NG, CT, and HIV were found in 8.0%, 2.0%, 3.0%, and 2.0%, respectively, and were more prevalent in younger women. HR-HPV was positive in 36.7%; 2 were positive for HPV18, but none for HPV16. Coinfection of HPV with other STIs was 8.3%. Prevalence of abnormal vaginal flora (AVF) was 82.5%, mostly bacterial vaginosis (BV) 54.6%, and moderate/severe aerobic vaginitis (msAV) 25.8%. HR-HPV was not related to BV (p = 0.67 ). The association of abnormal Pap test with msAV was not significant (p = 0.08 ). Conclusion . The prevalence of NG, CT, TV, and HR-HPV was according to expected, while that of HR-AVF was higher. The surprisingly low prevalence of HPV16 and HPV18 must be considered in the design of programs for prevention and vaccination; this setting can be useful as a model for postvaccination scenarios.